Multi-Attribute Decision Making Approach Based on Neutral Membership Degree of Picture Fuzzy Set - Amalendu, Si; Dan, Surajit; Das, Sujit (International Journal of Computer Sciences and Engineering, 2026)
In this study we proposed a new weighted aggregation operator for ranking the picture fuzzy numbers (PFNs) which is based on neutral membership value of PFN. As the picture fuzzy set (PFS) is an extension version of intuitionistic fuzzy set theory with introducing the neutral membership value during data analysis. The neutral membership value in PFS reflecting the ambiguous nature of the subject to judgment. The ambiguity is depending on the neutral membership value of PFN. The proposed weighted aggregation operator manages the ambiguity according to neutral membership value. Then, the aggregation operator applies in a multi attribute decision making method where attribute value of the alternative are picture fuzzy numbers. In the decision making process, the weight of attributes are calculated according to neutral values and aggregate the multiple attributes into a single PFN. Then estimate the individual score value of the alternatives. Lastly, ranking the alternative according to score value. Finally, a practical example for students’ performance in the multiple paper examination is highlighted for verifying the developed approach and demonstrates its practicality and effectiveness.